KEPUASAN PENGGUNA JASA TRANSPORTASI UNTUK MENINGKATKAN LOYALITAS - Saribanon, Euis; Sitanggang, Rohana; Amrizal, Amrizal (Sekolah Tinggi Manajemen Transportasi (STMT) Trisakti, 2016)
This study aims to analyze and describe the direct and indirect effects between service quality and ticket fare through customer satisfaction to achieve customer loyalty of Perum DAMRI Land Transport service at central office /Prime Pull Perum Damri in Jakarta. The population is Perum DAMRI customers who have used the services of Perum DAMRI several times for several destinations. While the sample is Perum DAMRI customers in the Region of DKI Jakarta of 125 respondents, using purposive sampling. The analysis used in this research is Path Analysis Method. The calculations indicate that the variables of service quality to customer satisfaction is significant. Based on calculations, it is indicated that the ticket fare variable to consumer satisfaction is significant. Consumer satisfaction can be an intervening variable between service quality and loyalty of consumers. Consumer satisfaction can be an intervening variable between the ticket fare to the customersâ loyalty. Based on the test results, the variable of consumer satisfaction on customer loyalty is significant, Adjusted R Square (R2) of 0.981 shows that 98.1 % of the variance or consumer loyalty is determined by the independent variables and intervening variables in the regression equation